2012
DOI: 10.1016/j.ajhg.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Calmodulin Cause Ventricular Tachycardia and Sudden Cardiac Death

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a devastating inherited disorder characterized by episodic syncope and/or sudden cardiac arrest during exercise or acute emotion in individuals without structural cardiac abnormalities. Although rare, CPVT is suspected to cause a substantial part of sudden cardiac deaths in young individuals. Mutations in RYR2, encoding the cardiac sarcoplasmic calcium channel, have been identified as causative in approximately half of all dominantly inherited CPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
345
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(361 citation statements)
references
References 37 publications
12
345
0
4
Order By: Relevance
“…We applied the higher‐throughput TileSeq approach, coupled with yeast complementation, to a diverse set of genes: SUMO1, for which heterozygous null variants are associated with cleft palate (Andreou et al , 2007); thiamine pyrophosphokinase 1 (TPK1), associated with vitamin B1 metabolism dysfunction (Mayr et al , 2011); and CALM1, CALM2, and CALM3, associated with cardiac arrhythmias (long‐QT syndrome (Crotti et al , 2013) and catecholaminergic polymorphic ventricular tachycardia (Nyegaard et al , 2012)). Because the three calmodulin genes encode the same polypeptide sequence, performing DMS for CALM1 also provided maps for CALM2 and CALM3.…”
Section: Resultsmentioning
confidence: 99%
“…We applied the higher‐throughput TileSeq approach, coupled with yeast complementation, to a diverse set of genes: SUMO1, for which heterozygous null variants are associated with cleft palate (Andreou et al , 2007); thiamine pyrophosphokinase 1 (TPK1), associated with vitamin B1 metabolism dysfunction (Mayr et al , 2011); and CALM1, CALM2, and CALM3, associated with cardiac arrhythmias (long‐QT syndrome (Crotti et al , 2013) and catecholaminergic polymorphic ventricular tachycardia (Nyegaard et al , 2012)). Because the three calmodulin genes encode the same polypeptide sequence, performing DMS for CALM1 also provided maps for CALM2 and CALM3.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, although CaM is essential in yeast, CaM gene knockout can be rescued with a vertebrate CaM, which is only 60% identical (62,63). Additionally, it appears that yeast can survive with Ca 2+ binding knocked out in all four EF-hands (34), whereas single mutations in just one of the three identical copies of CaM present in humans can cause major diseases (4)(5)(6). Yeast is therefore more robust to changes in CaM sequence than vertebrates, and this robustness probably translates into the higher evolutionary rate within ascomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans it binds to more than 300 targets (1)(2)(3). Humans have three genes that encode identical CaM proteins, but mutations in just one of the three copies can cause disease (4)(5)(6)(7)(8), as can altered gene expression (9). Although CaM has been extensively studied, many details about its function are still poorly understood.…”
mentioning
confidence: 99%
“…Several studies have shown that a disturbed CaM/RyR2 interaction plays a key role in arrhythmia and heart failure (8)(9)(10). CaM binding properties of the RyRs have focused on RyR1.…”
Section: Introductionmentioning
confidence: 99%